An investigation of the assessment of the continuous assessment portfolio component of art, craft and designs in Botswana junior secondary schools - Kontle, Bitha (School of Education, 2018)
In this study, I undertook to investigate how the requirements of formative and summative assessment influence the practices of teachers of art, craft and design in Botswana junior secondary schools (BJSS) in relation to the continuous assessment portfolio (CAP). I used qualitative research methods for data collection, mainly using in-depth interviews with individual teachers of art, craft and design. I also used grounded theory approach to interpret and analyse the collected data. The sample was chosen from different junior secondary schools near Gaborone, in Botswana. Interviewees had common qualification entry requirements while their experiences and backgrounds were different. The theoretical and conceptual frames underpinning the study are mainly Bourdieu's theory of practice and Lave and Wenger's theory of communities of practice. I focused my study on using these theoretical and conceptual frames to help describe the basis for the participants' choice in their judgements during their development of students' CAP. The outcome of this study makes claim that the teachers of art, craft and design who participated in the study clearly understood the requirements of the CAP. However, they chose to ignore these requirements due to the pressures originating from the tensions between formative assessment at school level and summative assessment at the level of the national examinations. These choices result in teachers undertaking activities which emphasize doing well in the national examinations rather than developing the students' skills for future use. This practice results from teachers' efforts to gain recognition for themselves and their schools as a result of outstanding national examination results. Good performance by their students in national examinations enhances their reputation as teachers and makes them eligible to be entrusted with national responsibilities such as being appointed moderators and examiners.